Islamic Inheritance : A Sentiment Analysis On 80 Literatures - Aam (SMART Insight, 2021)
This study tries to review Islamic Inheritance (Mawaris) research in Islamic economics and finance. It uses descriptive statistical analysis based on selected 80 article publications. The entire sample publications have published from 1976 to 2019. This study analyzes the number of publications based on journal and year, the top authors, the top-cited paper, and the sentiment analysis. The results show that the research of Islamic inheritance throughout the world has a high-positive sentiment of 1%, a positive sentiment of 24%, a negative sentiment of 44%, a high-negative sentiment of 0%, and the rest have a neutral sentiment of 31%. Also, the number of sentiments for these studies has increased in the world community, the largest number of high-positive sentiments occurred in 2014, the largest number of positive sentiments occurred in 2018, the largest number of neutral sentiments occurred in 2017 and 2018, and the largest number of negative sentiments occurred in 2017.